Creation laboratory in the midst of pandemic chaos: Visualities and costumes of the black character (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The wait for the event, the search for creation with ethics and respect for the history and trajectory of the black character. This account brings the experience lived in the classroom and the expectations of how to create costumes for and about black bodies. Here we present facts caused by the pandemic and the overcoming of the student body that, amidst the chaos, sought strength to create and design costumes for the black character who for many centuries was invisible on the stages of Brazilian theaters. The report presented is part of the doctoral thesis that is in the research phase.
Keywords: Pandemic; Creation process; Costume